Agro-morphologic Characters and Protein Content of Some Wheat (Triticum aestivum L.) Cultivars Grown at Different Sowing Dates in Sudan - Mohamedahmed, Esam Mahgoub; El Siddig, Marmar A.; El Hussein, Adil A.; Mohammed ali, Mohammed A. (University of Khartoum Journal of Agricultural Sciences, 2021)
High temperature is one of the major limiting factors in wheat production. Climate change accompanied by increasing temperature affect wheat grain yield in Sudan as in many other tropical countries. The aim of this research was to evaluate the response of six bread wheat (Triticum aestivum L.) cultivars to heat stress, based on morphological and protein content. A field experiment was conducted for two successive seasons (2014/2015 and 2015/2016) during which seeds were sown at three different sowing dates (early, medium and late) to subject the crop to different levels of temperature. To screen and assess performance of cultivars the agro-morphological characters, yield and yield-components traits as well as the protein content were used. Results indicated that sowing wheat cultivars at early date (9th November) achieved the highest grain yield, while sowing at a late date (16 December) significantly (P≤ 0.05) reduced grain yield, grain filling period, plant height, number of spikes/m2, kernels per spike and 1000-kernal weight compared to sowing at 9th November due to heat stress. Cultivars Condor, Debeira and Argeen produced the highest: grain yield, number of spikes per m2, number of kernal per spike and the heaviest kernels weight, while Sasaraib and El Neelain, followed by Condor and Argeen had the highest mean protein content (PC%) during the two seasons. Cluster analysis based on the agromorphological data divided the six wheat cultivars according to their response to different levels of heat, into three groups at 0.95 level of similarity with no clear correlation between these characters and the sowing date.